1999
DOI: 10.1007/s101030050032
|View full text |Cite
|
Sign up to set email alerts
|

The Monitoring of ALA-Induced Protoporphyrin IX Accumulation and Clearance in Patients with Skin Lesions by In Vivo Surface-Detected Fluorescence Spectroscopy

Abstract: The method of surface-detected fluorescence has been used to monitor the emission intensity from 5-aminolaevulinic acid (ALA)-induced protoporphyrin IX (PpIX) in lesions and corresponding adjacent normal skin. Three types of lesions were examined: psoriatic plaques, actinic keratosis and basal cell carcinoma. This study included a total of 14 human volunteers on whom ALA-induced PpIX formation and clearance was monitored for a total of 48 h post-ALA application. Both an ALA dose-ranging study, as well as a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…Biopsied tissues containing BCCs had substantial amounts of PpIX, but with some variability. While we did not measure how long PpIX was retained in tumor tissue it has been reported elsewhere [25] that the half-life of PpIX, determined spectroscopically in a single BCC, was 48 hours. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biopsied tissues containing BCCs had substantial amounts of PpIX, but with some variability. While we did not measure how long PpIX was retained in tumor tissue it has been reported elsewhere [25] that the half-life of PpIX, determined spectroscopically in a single BCC, was 48 hours. …”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that it was very difficult to determine the relative amounts of tumor and normal tissue in each biopsy and that this may, in part, explain the wide range of PpIX concentrations. Golub et al [25] also reported considerable variability in PpIX levels, measured spectroscopically, in human actinic keratosis, psoriatic lesions, and BCC following topical 5-ALA.…”
Section: Tissue Levels Of Photosensitizersmentioning
confidence: 99%
“…The AK lesion CR rates for the blue lightþVehicle alone arm in that large study was 35% [8]. In the small study described herein, the AK response to blue lightþVehicle alone arm was 12%, whereas results of AK lesions treated with Vehicle and exposed to ambient light was 24%.…”
mentioning
confidence: 88%
“…The instrumentation previously described for in vivo studies of fluorescence (Golub et al, 1998) was modified slightly for use in vitro. In brief, quasi-monochromatic 410 nm light was directed onto confluent monolayers of cells in 96-well plates by passing the light through one limb of a bifurcated optical fibre bundle whose common end was directed upward through a small hole in a table over which individual wells in the 96-well plates could be positioned for fluorescence measurements.…”
Section: Ala-induced Ppix Fluorescence Quantitated By Spectrophotoflumentioning
confidence: 99%